Chrysosoma from Vietnam, with description of a new species and a key to Vietnamese species (Diptera: Dolichopodidae) - Wang, Jinjing; Zhang, Lili; Yang, Ding (Zootaxa, 2012)
Six species of Chrysosoma Guérin-Méneville are recorded from Vietnam, including Chrysosoma vietnamense sp. nov. A key to the species of the genus from Vietnam is given for the first time.